Family Rights in Pakistan: Intersecting International Obligations and Plural National Legal Frameworks - Haroon Khalid (Indus Journal of Social Sciences, 2025)
This study analyzes the evolution and challenges to family rights in Pakistan through a historical lens, focusing on the plural legal system and the influence of international human rights commitments. It critiques how family law in Pakistan, originating from the Constitution, Islamic jurisprudence, statutes, and customary practices, interacts with the requirements of global treaties such as Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), the Convention on the Rights of the Child (CRC), and the International Covenant on Civil and Political Rights (ICCPR). Drawing on legal pluralism, feminist legal theory, and transnational legal-process theory, the study evaluates the domestic legal norms and international standards with a focus on gender equity and child protection, highlighting inconsistencies and areas of normative overlap. It works through doctrinal legal analysis, interpretation of case law, and treaty body reporting to scrutinize how Pakistan's legal and policy structure responds to international scrutiny. It also examines accountability mechanisms, such as the Universal Periodic Review (UPR) and the European Union (EU) GSP+ regime's impact on promoting legal reforms. Political resistance, cultural stigma, and disjointed implementation across the provinces are found to impede reform efforts despite some observable successes. Sustainable processes of legal reform must engage institutional capacity-building, civil-societal input, and culturally sensitive legal reforms in order to connect international obligations to national contexts meaningfully. The findings provide a framework for synchronizing family law reforms within a plural legal context while fostering compliance with global human rights norms.